A dynamic bidding strategy of hybrid energy storage system participating in day-ahead frequency regulation market. (15th December 2022) - Tang, Rongchuan; Xu, Qingshan; Fang, Jicheng; Jiang, Anni
Abstract: The rapid proliferation of intermittent and unpredictable renewable resources poses an unprecedented challenge to frequency stability in the modern system. A hybrid energy storage system (HESS) typically comprised of battery and ultracapacitor has better performance in quick response. In this context, this paper elaborates on a dynamic bidding strategy for an independent HESS operator to provide frequency regulation service in a day-ahead performance-based market. The proposed framework aims to maximize the net profit of the HESS operator based upon a two-part settlement mechanism considering the HESS degradation. Furthermore, the separated optimization of the battery and ultracapacitor can be realized by introducing a VSQF frequency division algorithm to leverage the full advantage of the HESS. Also, the optimization process in each stage can be innovatively driven by an improved snake optimizer and a penalty function is utilized to fulfilling the HESS-related and market-related constraints. The comparison between the HESS and the battery energy storage system (BESS) shows that HESS has indeed economic superiority and yields an 18.59 % higher profit. Moreover, the economic benefits under conservative SoC management by the flexible adjustment of the penalty coefficient are 9.06 % higher than that with the strict terminal SoC constraint which verifies the effectiveness of the dynamic bidding. Highlights: A VSQF frequency division algorithm is adopted to decouple the regulation signal. A dynamic bidding strategy is proposed based on the HESS operation mode. An improved snake optimizer provides a viable solution to the optimal bidding model. The terminal SoC management enables the continuous operation of HESS.